2007
DOI: 10.1111/j.1423-0410.2007.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the thrombin‐generating capacity, evaluated by thrombogram, and clot formation evaluated by thrombelastography of platelets stored in the blood bank for up to 7 days

Abstract: The kinetics of thrombin generation, as evaluated by CAT, correlates with the thrombus generation, as evaluated by thrombelastography and this may in part explain the clinical utility of the TEG in identifying clinically relevant coagulopathies, secondary to impaired thrombin generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…This explicitly demonstrates that plasma is needed in the aggregation response of the Multiplate assay. In-vitro studies evaluating the haemostatic potential in platelet concentrates during storage commonly use dilution of platelet concentrates to a fixed platelet concentration with FFP before haemostatic evaluation [5,41]. In the present study it was demonstrated that undiluted platelet concentrates after 7 days of storage displayed almost absent aggregation response upon stimulation with TRAP and very interestingly, the aggregation potential was recovered (back to day 1 levels) simply by readding FFP.…”
Section: Effect Of Red Blood Cells In Multiplatementioning
confidence: 83%
See 1 more Smart Citation
“…This explicitly demonstrates that plasma is needed in the aggregation response of the Multiplate assay. In-vitro studies evaluating the haemostatic potential in platelet concentrates during storage commonly use dilution of platelet concentrates to a fixed platelet concentration with FFP before haemostatic evaluation [5,41]. In the present study it was demonstrated that undiluted platelet concentrates after 7 days of storage displayed almost absent aggregation response upon stimulation with TRAP and very interestingly, the aggregation potential was recovered (back to day 1 levels) simply by readding FFP.…”
Section: Effect Of Red Blood Cells In Multiplatementioning
confidence: 83%
“…Given the strong clinical importance of whole blood haemostasis analyzers [1][2][3][4], these assays are applied increasingly for in-vitro evaluation of the haemostatic potential of stored platelets as a means of quality control, as the primary objective of platelet transfusion is to provide sufficient haemostatic activity in vivo to restore haemostasis. Most of these in-vitro investigations are based on platelet concentrates, that is platelets in suspension with plasma and additive solution [5][6][7]. Hence, the contribution of red blood cells (RBCs) is generally not considered when evaluating the in-vitro haemostatic potential of platelet concentrates, even though the platelet concentrates are rejuvenated in whole blood (that contains RBC) and massive transfusion protocols recommend that the hematocrit (hct) should be held above 0.30 to obtain optimal haemostasis in vivo [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, coagulation competence was evaluated by TEG, as it provides more clinically relevant information than prothrombin and activated partial thromboplastin times [28,29]. Withdrawal of 450 ml blood reduced the time until initial fibrin formation by $20% without altering clot strength, and withdrawal of an additional 450 ml blood further increased coagulation activity as evaluated by a-Angle, which reflects the thrombin generation of the haemostatic process [30]. Thus, this study demonstrates that a blood loss by itself activates the coagulation system as suggested by orthostatic stress [2,3,5] and lower body negative pressure [4].…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawing 450 ml blood reduced the time until initial fibrin formation (R: 6.5 W 0.9 to 5.1 W 1.0 min, P < 0.01), whereas the rate of clot formation increased after withdrawal of 900 ml blood (a-Angle: 66 W 4 to 70 W 3 deg, P < 0.01). Clot strength (maximal amplitude: 57 W 4 mm), clot lysis 30 min after maximal amplitude (LY 30 : 0.8% [0-3.5%] (median [range])), and platelet count (218 W 25 T 10 9 l S1 ) were unaffected. For supine males, $25% of a moderate blood loss is compensated by fluid recruitment to the circulation, which may explain the minor cardiovascular response.…”
mentioning
confidence: 94%
See 1 more Smart Citation